The Relationship Between Multi-cultural Leadership and Administrative Effectiveness of School Administrators Under Narathiwas Primary Educational Area, Office 3 - เตี้ยนวล, ปิยนันท์ (Al-HIKMAH Journal, 2021)
This study aimed to 1) investigate multi-cultural leadership of school administrators under Narathiwas Primary Educational Area, Office 3, 2) investigate administrative effectiveness of school administrators under Narathiwas Primary Educational Area, Office 3, and 3) study relationship between multi-cultural leadership and administrative effectiveness of school administrators under Narathiwas Primary Educational Area, Office 3. The sample consisted of 310 teachers who worked in primary schools under Narathiwas Primary Educational Area, Office 3, chosen through the use of Krejcie and Morgan’s table, the stratified random sampling and simple random sampling techniques. Research tools were five-scale questionnaires and statistics for the study included percentage, mean, standard deviation and Pearson’s product moment correlation coefficient. The study revealed the following results. 1) Multi-cultural leadership of school administrators under Narathiwas Primary Educational Area, Office 3 was at the highest level, both overall picture and each aspect. The aspect that received the highest mean score was cultural diversity, followed by vision on educational equality, and state of excellence, cultural acceptance, social justice and elimination of differences, and communicative ability consecutively. 2) Administrative effectiveness of school administrators under Narathiwas Primary Educational Area, Office 3 was at the highest level, both overall picture and each aspect. The aspect that received the highest mean score was maintenance of organizational values, self-adjustment, integration and target reaching consecutively. 3) The relationship between multicultural leadership and administrative effectiveness of school administrators under Narathiwas Primary Educational Area, Office 3 was significantly and highly positive at the .01 level.